FITUR PING MOBILE LEGENDS - Sumarso, Diana Perwitasari; Wati, Sukarela; Setiawan, Koesworo (JURNAL KOMUNIKATIO, 2019)
This study discusses the students who use the Ping Mobile Legends online game feature, the method used is quantitative descriptive method and tested using Rank Sperman correlation. The research sample are Djuanda University communication science students consisting of 20 users of the Mobile Legends online game. The results of the study shows that (1) Users often use the Ping feature because it is only a click away, (2) The ping feature is often used by team players because it is easy, (3) The ping feature is the most favorite feature of every player, (4) The ping feature can smooth the game only with a click. The ping feature is very superior compared to other features and has the largest interpretation number 4 and is categorized well.Â Keywords: Ping Features, Online Games, Students, Mobile Legends.